Everyday‐like memory for objects in ageing and Alzheimer's disease assessed in a visually complex environment: The role of executive functioning and episodic memory. Issue 1 (13th October 2014) - Sauzéon, Hélène; N'Kaoua, Bernard; Pala, Prashant Arvind; Taillade, Mathieu; Auriacombe, Sophie; Guitton, Pascal
Abstract : To investigate everyday memory, more and more studies rely on virtual‐reality applications to bridge the gap between in situ approaches and laboratory settings. In this vein, the present study was designed to assess everyday‐like memory from the virtual reality‐based Human Object Memory for Everyday Scenes (HOMES) test (Sauzéon et al ., 2012, Exp. Psychol ., 59, 99) in ageing and in Alzheimer's disease (AD). Two aims motivated this study: the first was to assess multiple processes of episodic memory (EM) functioning embedded within contexts closely related to real life in ageing and AD using the multi‐trial free‐recall paradigm, and the second aim was to evaluate the mediating effects of executive functioning (EF), EM, and subjective memory complaints (SMCs) on age differences in the HOMES measures and in AD. To this end, the HOMES test and neurocognitive tests of EF and EM were administered to 23 younger adults, 23 older adults, and 16 patients with AD. The results were: firstly, compared to young adults, elderly adults presented only free‐recall decline that almost disappeared in recognition condition whereas AD patients exhibited a poor clustering, learning, and recognition performance, and also a high amount of false recognition; secondly, age differences as well as AD related deficits on the HOMES test were mediated by both memory and EF measure while those observed on false memory indices were only mediated by EM measure; thirdly, the HOMES indices are related to SMCs even when episodic or EF measures are controlled. Overall, the results supported the fact that the VR‐based memory test is an appropriate device to capture age‐related differences as well as the AD effect with respect to both in situ and laboratory settings.